Documentation of Accounting Records in Light of Legislative Innovations - K. V. Bezverkhiy (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Legislative reforms in accounting aim to simplify accounting records and compilation of financial reports by business entities, thus increasing the position of Ukraine in the global ranking of Doing Business. This simplification is implied in the changes in the Regulation on Documentation of Accounting Records, entered into force to the Resolution of the Ukrainian Ministry of Finance. The objective of the study is to analyze the legislative innovations involved. The review of changes in documentation of accounting records is made. A comparative analysis of changes in the Regulation on Documentation of Accounting Records is made by sections: 1) General; 2) Primary documents; 3) Accounting records; 4) Correction of errors in primary documents and accounting records; 5) Organization of document circulation; 6) Storage of documents. Methods of analysis and synthesis are used for separating the differences in the editions of the Regulation on Documentation of Accounting Records. The result of the study has theoretical and practical value for the domestic business enterprise sector.